Stem cell markers: ABCG2 and MCM2 expression in retinoblastoma. Issue 7 (23rd March 2006) - Mohan, A; Kandalam, M; Ramkumar, H L; Gopal, L; Krishnakumar, S
Abstract : Backgound/aim: The authors studied the expression of cancer stem cell surface marker, ABCG2, and neural stem cell marker, MCM2, in retinoblastoma and correlated clinicopathologically. Methods: Among 39 retinoblastomas, 18 tumours were not subjected to preoperative/postoperative chemotherapy, 15 tumours underwent postoperative chemotherapy, and six tumours had preoperative chemotherapy. There were 20 tumours with no invasion and 19 tumours with invasion of choroid/optic nerve. ABCG2 and MCM2 expression was studied by immunohistochemistry. Results: ABCG2 was positive in six of six and MCM2 was positive in five of six tumours that had recurred in the orbit or metastasised. ABCG2 was positive in 15/19 tumours with invasion. MCM2 was positive in 16/19 tumours with invasion. Invasive tumours showed higher expression of ABCG2 (p<0.01) and MCM2 (p<0.01) proteins. There was no correlation with differentiation and laterality of the tumours. Non-neoplastic retina was positive for ABCG2 and MCM2. Conclusion: ABCG2 and MCM2 were expressed more in invasive tumours. Further studies are needed to understand the significance of ABCG2 and MCM2 expression in retinoblastoma.